Når Guds engle er onde - Andersen, Rikke Hvarregaard (Dansk Teologisk Tidsskrift, 2016)
The aim of this article is to re-examine the claim that the Book of Jubilees and two Qumran texts, the Community Rule and the Damascus Document, have been influenced by the myth of the fallen angels as found in the Book of the Watchers. The analysis focuses on the problem of evil and examines of what sin consists, who is held responsible for it, and how human nature is understood. Even if dependence on the Book of the Watchers is likely, the motifs have undergone radical changes in the three other texts, and it would be more precise to describe the influence as limited.